1974
DOI: 10.1063/1.1655464
|View full text |Cite
|
Sign up to set email alerts
|

Electrically variable diffraction in spherulitic liquid crystals

Abstract: An electrically controllable diffraction mode in liquid crystals is described. The variable grating is a stable single layer of small uniform birefringent spherulitic domains imbedded in a homeotropic matrix. The size of the domains is changed by small dc or ac voltages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…3(a) and 3(b)), whereas, at the far zone, they are a manifestation of the spatial periodicity of the bubbles. 18,25 At the far zone, the diffraction pattern is composed of a series of welldefined bright spots that represented the Fourier transform of the bubble distribution in the plane of the cell. Figures 4(a) and 4(b) show the experimental and calculated diffraction patterns of the bubble structure of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a) and 3(b)), whereas, at the far zone, they are a manifestation of the spatial periodicity of the bubbles. 18,25 At the far zone, the diffraction pattern is composed of a series of welldefined bright spots that represented the Fourier transform of the bubble distribution in the plane of the cell. Figures 4(a) and 4(b) show the experimental and calculated diffraction patterns of the bubble structure of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These bubbles can arrange themselves in hexagonal arrays. Such formation of bubble arrays was observed for the first time in 1974, simultaneously by both Kawachi et al 17 and Haas et al 18 in liquid crystal materials with negative dielectric anisotropy. Both groups noted that CLCN bubbles were generated by applying a DC or AC electric pulse strong enough and with a suitable frequency to induce electrohydro-dynamical effects.…”
Section: Introductionmentioning
confidence: 88%
“…We have found that some of the studied laser-generated structures can also be obtained spontaneously when cooling the samples from the isotropic phase (although less reliably and without the control of spatial locations) and after applying low-frequency (10 Hz) electric fields to induce hydrodynamic instability. These localized structures, along with torons and hopfions, are several members of the large family of so-called cholesteric bubbles that were typically studied when occurring spontaneously, but not well understood in past experimental works [20,[34][35][36][37][38][39][40][41][42][43][44]. We note that the study of axially symmetric cholesteric configurations reported here is not exhaustive.…”
Section: Nested Axially Symmetric Structures Of Multiple Torons Anmentioning
confidence: 86%
“…Such developments can be viewed as spatially controlled versions of randomly distributed defect structures generated by uniform quasistatic electric fi elds as shown in Refs. [ 8,9 ] four decades ago, see also Ref. [ 10,11 ] for more recent works.…”
Section: Doi: 101002/adma201400811mentioning
confidence: 98%